(untitled) (Web of Teachers: Inderscience Research, 2025)
This literature review explores the global research on discourse markers (DMs) in the English language, focusing on their definitions, functions, and variations across contexts. Drawing from key theoretical models and empirical studies, the article highlights how DMs operate in spoken and written English, their sociolinguistic variability, and the challenges they present for language learners. The review also emphasizes the importance of teaching DMs explicitly in ESL/EFL settings. Findings suggest that while discourse markers are often overlooked, they play a vital role in ensuring coherence, fluency, and naturalness in communication. Recommendations for future research are provided, particularly in the areas of digital discourse and second language acquisition.